Synthesis and anticancer activity of podophyllotoxin derivatives with nitrogen-containing heterocycles - Yin, Meng; Fang, Yongsheng; Sun, Xiaotong; Xue, Minggao; Zhang, Caimei; Zhu, Zhiyun; Meng, Yamiao; Kong, Lingmei; Myint, Yi Yi; Li, Yan; Zhao, Jingfeng; Yang, Xiaodong (Frontiers in Chemistry, 2023)
Three series of podophyllotoxin derivatives with various nitrogen-containing heterocycles were designed and synthesized. The antitumor activity of these podophyllotoxin derivatives was evaluated in vitro against a panel of human tumor cell lines. The results showed that podophyllotoxin-imidazolium salts and podophyllotoxin-1,2,4-triazolium salts a1-a20 exhibited excellent cytotoxic activity. Among them, a6 was the most potent cytotoxic compound with IC50 values of 0.04-0.29 μM. Podophyllotoxin-1,2,3-triazole derivatives b1-b5 displayed medium cytotoxic activity, and podophyllotoxin-amine compounds c1-c3 has good cytotoxic activity with IC50 value of 0.04-0.58 μM. Furthermore, cell cycle and apoptosis experiments of compound a6 were carried out and the results exhibited that a6 could induce G2/M cell cycle arrest and apoptosis in HCT-116 cells.